Optimization of Collector Systems of Technological Gyrotrons with Shielded Magnetic Systems - Morozkin, M. V.; Proyavin, M. D.; Manuilov, V. N.; Glyavin, M. Yu (Radiophysics and quantum electronics, 2020)
We analyze the motion of the electron beam in the collector of a gyrotron with the shielded magnetic system. The methods of optimization of the collector are proposed, depending on the limitations imposed on its transverse dimensions. Calculations are performed for collectors of the technological gyrotrons capable of operating in a wide range of magnetic fields (1.0–1.8 T), which allows generating radiation at a frequency of 24 to 48 GHz at the fundamental cyclotron resonance and, correspondingly, up to 100 GHz when exciting oscillations at the second gyrofrequency harmonic.